61. Altered recovery from inhibitory repetitive Transcranial Magnetic Stimulation (rTMS) in subjects with photosensitive epilepsy. Issue 12 (December 2016) - Bocci, T.; Caleo, M.; Restani, L.; Barloscio, D.; Parenti, L.; Rossi, S.; Sartucci, F.
Abstract : To investigate functional changes underlying photosensitivity, we studied the response of the visual cortex to low-frequency, inhibitory repetitive Transcranial Magnetic Stimulation (rTMS) in patients with photosensitive seizures and healthy volunteers. Visual evoked potentials (VEPs) triggered by grating stimuli of different contrasts were recorded in both hemispheres before and after functional inactivation of the occipital cortex of one side via low-frequency rTMS (0.5 Hz for 20 ′ ). VEPs were recorded before (T0), immediately after (T1) and 45 ′ following the completion of rTMS (T2). Baseline amplitudes of the early VEP components (N1 and P1) were enhanced in photosensitive subjects. At T1, rTMS produced an inhibitory effect on VEPs amplitudes at all contrasts in the targeted side, and a concurrent facilitation of responses in the contralateral hemisphere. While the relative variation with respect to pre-rTMS values was similar in photosensitive patients and controls at T1, robust changes appeared in the recovery phase (T2): visual responses recovered more quickly in the stimulated hemisphere, and disinhibition persisted in the contralateral side of photosensitive subjects. The rapid recovery of excitability and the persistent transcallosal disinhibition following perturbation of cortical activity may play a role in the pathophysiology of photosensitive epilepsy.